2009
DOI: 10.1111/j.1745-4549.2009.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF FROZEN PERIOD ON THE PROXIMATE COMPOSITION AND MICROBIOLOGICAL QUALITY OF NILE TILAPIA FISH (OREOCHROMIS NILOTICUS)

Abstract: The rationale of the study was to investigate the influence of frozen period on quality of fish fillet. The proximate composition and microbiological analyses were carried out at 15 days interval on tilapia fish fillets during frozen storage. It was found that the protein, moisture and ash contents decreased significantly (P < 0.05) during the entire storage period. However, the fat content increased from 0.37 ± 0.01 to 0.56 ± 0.01 g/100 g of fillet. The total volatile bases nitrogen and pH values also increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
19
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 16 publications
10
19
4
Order By: Relevance
“…All minces reported TVB-N values lower than the official permitted limits (30 to 35 mg N/100 g). Unlike the present study, previous reports observed an increase of BVT-N content (80%) in frozen tilapia fillets during storage (Emire & Gebremariam, 2009) and 33% after the 60 th day of tilapia-sketelon mince freezing storage (Kirschnik et al, 2013). Peroxide values for washed mince were not determined due to its low lipid content.…”
Section: Physicochemicalcontrasting
confidence: 99%
“…All minces reported TVB-N values lower than the official permitted limits (30 to 35 mg N/100 g). Unlike the present study, previous reports observed an increase of BVT-N content (80%) in frozen tilapia fillets during storage (Emire & Gebremariam, 2009) and 33% after the 60 th day of tilapia-sketelon mince freezing storage (Kirschnik et al, 2013). Peroxide values for washed mince were not determined due to its low lipid content.…”
Section: Physicochemicalcontrasting
confidence: 99%
“…This work found a higher moisture content (87.36% ± 1.16) than reported by Emire and Gebremariam () (79.87%) and Garduño‐Lugo and others () (79.1%). The possible explanation of this may be the day of analysis.…”
Section: Resultsmentioning
confidence: 99%
“…According to Arekemase et al (2012), protein content of fresh samples of tilapia ranged from 15.56 to 15.72% and fat content ranged from 5.12 to 5.44%. Emire and Gebremariam (2010) reported 79.87% moisture content, 18.52% protein, 0.37% fat and 0.98% ash in Nile tilapia fish fillets. In the present study, the fat content of tilapia samples was higher which could be attributed to an influence of diet.…”
Section: Nutritional Profilementioning
confidence: 96%
“…Rong et al (2009), Emire and Gebremariam (2010), Arekemase et al (2012) and Kulawik et al (2013) have reported on the quality and shelf life of tilapia under low temperature storage. However, so far only Laly et al (2016) have reported on the quality changes of monosex tilapia during storage.…”
Section: Introductionmentioning
confidence: 99%